Psychotherapy versus the combination of psychotherapy and pharmacotherapy in the treatment of depression: a meta-analysis - Cuijpers, Pim; van Straten, Annemieke; Warmerdam, Lisanne; Andersson, Gerhard (Depression and anxiety, 2009)
Background: A large number of studies have shown that psychological treatments have significant effects on depression. Although several studies have examined the relative effects of psychological and combined treatments, this has not been studied satisfactorily in recent statistical meta‐analyses. Method: We conducted a meta‐analysis of randomized studies in which a psychological treatment was compared to a combined treatment consisting of the same psychological treatment with a pharmacological therapy. For each of these studies we calculated the effect size indicating the difference between the psychological and the combined treatment. Results: All inclusion criteria were met by 18 studies, with a total of 1,838 subjects. The mean effect size indicating the difference between psychological and combined treatment was 0.35 (95% CI: 0.24∼0.45; P<0.001), with low heterogeneity. Subgroup analyses indicated that the difference between psychological and combined treatments was significantly smaller in studies in which cognitive behavior therapy was examined. We also found a trend (P<0.1) indicating that the difference between psychological and combined treatment was somewhat larger in studies aimed at specific populations (older adults, chronic depression, HIV patients) than in studies with adults, and in studies in which Trycyclic antidepressants or SSRIs were examined, compared to studies in which a medication protocol or another antidepressant was used. At follow‐up, no difference between psychological and combined treatments was found. Conclusion: We conclude that combined treatment is more effective than psychological treatment alone. However, it is not clear whether this difference is relevant from a clinical perspective. Depression and Anxiety, 2009. © 2008 Wiley‐Liss, Inc.